A transição incompleta: Horácio Lafer e a defesa do liberalismo na Constituinte de 1946 - Gomes, Caius Vinicius de Oliveira (2008)
The present paperwork aims at looking over the political debate at the 1946 constituent, from the view of the economical crisis figured by the end of the war and the consequent finish of the New State Dictatorship, aiming at understanding the impasses and dilemmas faced by the political actors upon the necessity of reorganization of the institutional frame concerning the economic policy. The liberal though was facing the hard task of redefining the huge presence of the State in the Brazilian economy e society. The debate upon the development of the industry was a guidance axle of the disputes observed in the Constituent. The study is based on Horacio’s Lafer ideas, considering him as a link between the two political experiences. The analysis of the parties, especially of the position taken upon the differences faced in the process of democracy rebuilding, was seen with attention by following the chancing process and continuation which characterized President Dutra’s administration.